Effects of Coffea canephora genotypes on the microbial community of soil and fruit - Willian dos Santos Gomes; Fábio Luiz Partelli; Tomás Gomes Reis Veloso; Marliane de Cássia Soares da Silva; Aldemar Polonini Moreli; Taís Rizzo Moreira; Lucas Louzada Pereira (Scientific Reports)
Abstract In recent years, the role of microbial communities in agricultural systems has received increasing attention, particularly concerning their impact on plant health and productivity. However, the influence of host plant genetic factors on the microbial composition of coffee plants remains largely unexplored. This study provides the first comprehensive investigation into how genotype affects the microbial communities present in the rhizosphere and fruits of Coffea canephora. Conducted on a commercial coffee farm in Brazil, we analyzed six genotypes of C. canephora var. Conilon. Soil and fruit samples were collected from which microbial DNA was extracted and sequenced, targeting the V3-V4 region of the 16 S rDNA and the ITS1 region for fungi. A total of 12,239,769 reads were generated from the 16 S rDNA and ITS1 regions. The PCoA revealed distinct patterns of beta diversity, with genotype 153 exhibiting significant isolation in soil bacterial communities. The dominant bacterial orders included Rhizobiales and Rhodobacterales, while the fungal community comprised diverse taxa from Saccharomycetales and Hypocreales. LEfSe analysis identified key metagenomic biomarkers, highlighting genotype Baiano 4 for its richness in fruit-associated taxa, whereas genotype 153 exhibited lower diversity in both soil and fruit samples. This work enhances our understanding of the microbiomes associated with different coffee genotypes, providing evidence of how host genetic variation influences microbial community composition. Our findings indicate that specific microbial taxa are enriched in the fruits and soil of various genotypes. Future research should focus on identifying these microorganisms and elucidating their specific functions within the rhizosphere and coffee fruits.